Penegakan Hukum Terhadap Tindak Pidana E-Commerce (Studi Kasus: Kepolisian Daerah Sumatera Barat) - Lesmana, Hendra; Yoserwan, Yoserwan; Mulyati, Nani (Lareh Law Review, 2024)
The crime of fraud is increasingly developing following the development of the times and technological advances. The legal regulations made to anticipate crimes in this case do not reduce the crime. One of them is the crime of e-commerce fraud which is growing rapidly in society. This can be proven by the West Sumatra Regional Police, with 130 reports received in terms of online-based fraud. The formulation of the problem is 1. How is the role of the West Sumatra Regional Police in enforcing the law on alleged e-commerce crimes? 2. How is the law enforcement against fraud with an e-commerce system in the West Sumatra Regional Police? 3. What are the obstacles and efforts faced by the West Sumatra Regional Police in enforcing the law on e-commerce crimes? In this writing, the author uses an empirical legal method. The research uses an empirical legal research method. From the results of the study, the role of the West Sumatra Regional Police in the criminalization of alleged e-commerce fraud is realized by receiving reports and complaints from the public, conducting investigations and investigations to provide legal protection for victims of alleged e-commerce fraud. This is realized through repressive and preventive actions. Law enforcement against alleged e-commerce fraud in the West Sumatra Regional Police based on the results of the study, out of 130 cases received, only 3 cases were able to be revealed that reached the prosecution stage, which was carried out by the West Sumatra Regional Police. The other 127 cases were stopped at the investigation stage due to constraints on evidence. Factors that influence law enforcement faced by the West Sumatra Police such as facilities and infrastructure, technology, banking secrets in this case become problems in revealing cases of e-commerce fraud. Keywords : e-commerce, fraud, law enforcement, police